Borreliacidal activity of Borrelia metal transporter A (BmtA) binding small molecules by manganese transport inhibition - Wagh D; Pothineni VR; Inayathullah M; Liu S; Kim KM; Rajadas J (Dove Medical Press, 2015)
Dhananjay Wagh,* Venkata Raveendra Pothineni,* Mohammed Inayathullah, Song Liu, Kwang-Min Kim, Jayakumar Rajadas Biomaterials and Advanced Drug Delivery Laboratory, Stanford Cardiovascular Pharmacology Division, Cardiovascular Institute, Stanford University School of Medicine, Palo Alto, CA, USA *These authors contributed equally to this work  Abstract: Borrelia burgdorferi, the causative agent of Lyme disease, utilizes manganese (Mn) for its various metabolic needs. We hypothesized that blocking Mn transporter could be a possible approach to inhibit metabolic activity of this pathogen and eliminate the infection. We used a combination of in silico protein structure prediction together with molecular docking to target the Borrelia metal transporter A (BmtA), a single known Mn transporter in Borrelia and screened libraries of FDA approved compounds that could potentially bind to the predicted BmtA structure with high affinity. Tricyclic antihistamines such as loratadine, desloratadine, and 3-hydroxydesloratadine as well as yohimbine and tadalafil demonstrated a tight binding to the in silico folded BmtA transporter. We, then, tested borreliacidal activity and dose response of the shortlisted compounds from this screen using a series of in vitro assays. Amongst the probed compounds, desloratadine exhibited potent borreliacidal activity in vitro at and above 78 µg/mL (250 µM). Borrelia treated with lethal doses of desloratadine exhibited a significant loss of intracellular Mn specifically and a severe structural damage to the bacterial cell wall. Our results support the possibility of developing a novel, targeted therapy to treat Lyme disease by targeting specific metabolic needs of Borrelia.  Keywords: Lyme disease, BmtA, Borrelia burgdorferi, desloratadine, Bac Titer-Glo assay